2020
DOI: 10.1002/ctm2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic validation and therapeutic decision‐making of the AJCC eighth pathological prognostic staging for T3N0 breast cancer after mastectomy

Abstract: Background T3N0 breast cancer might be a distinct clinical and biological entity, with higher heterogeneity and presenting diverse responses to locoregional and systemic therapy. The aim of the current study was to validate the prognostic effect and assess the treatment decision‐making of the American Joint Committee on Cancer (AJCC) eighth pathological prognostic staging in T3N0 breast cancer after mastectomy. Methods We retrospectively included 2465 patients with stage T3N0 breast cancer who had undergone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Regarding the treatment decision for chemotherapy, we also found that patients with T1-2N1M0 disease could obtain survival benefit from chemotherapy irrespective of the pathological prognostic stages [30]. Moreover, our previous study also observed a survival gain from chemotherapy in T3N0M0 BC patients with 8th AJCC stage IIIA disease but was not in those with stage IA, IB, and IIA diseases [31]. To the best of our knowledge, no studies investigated the effect of chemotherapy in T1-2N0M0 TNBC based on the 8th prognostic staging of AJCC.…”
Section: Tnbc Is a Specific Subtype Of Bc [24e26] In This Study Wementioning
confidence: 54%
See 1 more Smart Citation
“…Regarding the treatment decision for chemotherapy, we also found that patients with T1-2N1M0 disease could obtain survival benefit from chemotherapy irrespective of the pathological prognostic stages [30]. Moreover, our previous study also observed a survival gain from chemotherapy in T3N0M0 BC patients with 8th AJCC stage IIIA disease but was not in those with stage IA, IB, and IIA diseases [31]. To the best of our knowledge, no studies investigated the effect of chemotherapy in T1-2N0M0 TNBC based on the 8th prognostic staging of AJCC.…”
Section: Tnbc Is a Specific Subtype Of Bc [24e26] In This Study Wementioning
confidence: 54%
“…As mentioned above, many studies have fully explored the prognostic value of the new AJCC prognostic staging, but its guiding role in treatment decision-making is still not clear. Our previous studies had shown that the new AJCC staging might provide additional treatment decisions, including surgery and radiotherapy [17,30,31]. Regarding the treatment decision for chemotherapy, we also found that patients with T1-2N1M0 disease could obtain survival benefit from chemotherapy irrespective of the pathological prognostic stages [30].…”
Section: Tnbc Is a Specific Subtype Of Bc [24e26] In This Study Wementioning
confidence: 65%
“…В исследовании китайских ученых Wu S. et al [12] пациенткам с T3N0M0 РМЖ, стадированным по классификации TNM 7 версии, установили новые прогностические стадии согласно TNM 8 версии. С увеличением прогностической стадии снижалась ОСВ пациенток.…”
Section: Introductionunclassified
“…A valuable staging system should also provide effective guidance for selection of appropriate treatment. Previous studies have found that the new PPS may have an important role in treatment decision-making for stage I to III BC 10 , 11 . However, a recent study showed that PPS did not provide better discriminatory ability of risk stratification compared with the AS in T1-2N0M0 triple-negative BC, but PPS could more accurately predict the efficacy of chemotherapy 12 .…”
Section: Introductionmentioning
confidence: 99%